Don't Fence Me In (Symphony in the Flint Hills, 2017)
Introduction: Long before the first encounter between the cow horse and the iron horse, there was prairie as big as the Texas sky. Then came the machine that converted wheat and corn into cash. For a nation of farmers, the American dream was just a sturdy fence and rail line away.
Keywords: prairie; railroads; farmers